PUZZLE SABLON EDUKATIF, ARTISTIK, DAN BERBUDAYA - Didik Ari Supriyanto; Gusti Ngurah Kadek Wiranata; Muhammad Faizal; Salsabila Iftinan Ansari; Retno Purwandari (Corak : Jurnal Seni Kriya, 2021)
The toy products projected in this entrepreneurship program are toy products that aim to provide an introduction or education to children about the culture and arts in Indonesia which today have begun and are even forgotten by children today. This program is expected that apart from being a forum for entrepreneurship by starting a business, it can be an alternative and solution to maintain and preserve Indonesian culture and arts. "Educational, Artistic, and Cultured Screen Printing Puzzle" is a toy with a handmade concept that carries an educational theme, contributing to the field of education; artistic, attractive and aesthetic appearance; as well as cultured, because it raises the local traditions of the archipelago. This toy tries to invite children who are the younger generation who are the successors of the nation's hopes to know and understand the culture and arts that have been passed down from our ancestors, so that they can protect and preserve them. This puzzle is made from wood waste which is screened in the form of wayang figures, Indonesian cultural icons, and is equipped with descriptions of the screened cultural figures or icons. This toy can be a souvenir for tourists who come to visit Indonesia, because the picture or screen printing on the puzzle surface is in the form of pictures of Indonesian culture and art or something that really characterizes Indonesia. promotional media for the time being with an online system, such as using Facebook, Instagram, WhatsApp, and e-mail.Produk mainan yang diproyeksikan dalam program kewirausahaan ini adalah produk mainan yang bertujuan untuk memberikan pengenalan atau edukasi kepada anak- anak tentang kebudayaan dan kesenian yang ada di Indonesia yang dewasa ini sudah mulai dan bahkan terlupakan oleh anak-anak zaman sekarang. Program ini diharapkan selain sebagai wadah berwirausaha dengan merintis bisnis dapat menjadi alternatif dan solusi untuk menjaga dan melestarikan kebudayaan dan kesenian Indonesia. “Puzzle Sablon Edukatif, Artistik, dan Berbudaya” adalah mainan dengan konsep handmade yang mengusung tema edukatif, member andil dalam bidang pendidikan; artistik, tampilan menarik dan estetis; serta berbudaya, katena mengangkat tradisi lokal Nusantara. Mainan ini mencoba mengajak anak-anak yang merupakan generasi muda penerus harapan bangsa untuk mengenal dan memahami kebudayaan serta kesenian yang diwariskan leluhur kita, sehingga mereka bisa menjaga dan melestarikannya. Puzzle ini dibuat dari bahan limbah kayu yang disablon berupa tokoh-tokoh wayang, ikon-ikon kebudayaan Indonesia, serta dilengkapi dengan deskripsi dari tokoh atau ikon budaya yang disablon tersebut. Mainan ini bisa menjadi souvenir bagi turis yang datang berkunjung ke Indonesia, karena gambar atau sablon pada permukaan puzzle berupa gambar-gambar kebudayaan dan kesenian Indonesia ataupun sesuatu yang sangat mencirikhaskan Indonesia. Media promosi untuk sementara masih dengan sistem daring, seperti menggunakan facebook, instagram, whatsApp, dan surel.